CO-OPERATIVE MARITIME DIPLOMACY: THE RESOLUTION OF THE PHILIPPINES-INDONESIA MARITIME BORDER DISPUTE (1994-2014) - Anak agung Banyu perwita; Ircha Tri Meilisa (Department of International Relations, Universitas Andalas, 2018)
The formation of national integrity in the international circuit is essential for a state. National integrity can be seen by fixed territory where a state can exercise their sovereignty in certain area portrayed by a fix border with neighboring countries both in the land and sea. The Philippines has been claimed over its territory based on the Treaty of Paris as the result of the Spanish American war that ceded the sovereignty over the archipelago of the Philippines to the United State. With respect to its history, the Philippines faced the dilemma whether or not it should redefine its baseline law in accordance with the UNLOS provisions. This dilemma then leads to unclear territorial boundary with its neighboring country– Indonesia.Hence, this article aims to analyze the Philippines-Indonesia maritime border dispute in the Exclusive Economic Zone from Celebes to Mindanao sea. Using the neoliberalism perspective, the authors analyzed the interest of the Philippines to establish cooperation with Indonesia related to the national territory of each country, each legislation, maritime zones, and exercise of sovereignty over disputes maritime territories. Meanwhile, co-operative maritime diplomacy also used to determine the Philippines action in the form of bilateral cooperation, joint exercise on maritime security and regional cooperation to secure the Philippines and Indonesia maritime areas. On behalf of common interest, both countries succeed in maintaining their relations to achieve mutual goals regardless of boundaries. Furthermore, the foreign policy theory will also play an intervening role to explain the regulation about the dispute settlement efforts of delimitation boundary between the Philippines and Indonesia.